Influence of language learning anxiety on L2 speaking and writing of Filipino engineering students - Macayan, Jonathan Veran; Quinto, Edward Jay Mansarate; Otsuka, Julius C.; Cueto, Allyzsa Bernadette S. (Penerbit Universiti Kebangsaan Malaysia, 2018)
Feelings of anxiety, apprehension, and nervousness remain a prevailing phenomenon in learning a second or a foreign language. This explanatory sequential research examined the influence of language learning anxiety on students’ second language (henceforth L2) writing and speaking performance. A total of 162 students in an engineering University in Manila, the Philippines participated in the initial quantitative phase, in which they accomplished a self-developed scale adapted from Horwitz, Horwitz and Cope’s (1986) Foreign Language Classroom Anxiety Scale (FLCAS) to fit the context of the present investigation. Speaking and writing scores from an institutional English language test were also used as measures for the outcome variables. The analyses of variance yielded significant results for both anxiety on speaking [F(2,162)=43.35; p=0.00; ηp 2 =0.35] and anxiety on writing [F(2,162)=10.73; p=0.00; ηp 2=0.12]. The findings on the influence of language learning anxiety on speaking corroborate previous studies that found high levels of anxiety to have debilitative impact on L2 speaking. Interestingly, however, the influence of anxiety on writing reflects the less frequent facilitative impact of anxiety on language abilities found in a very small number of studies in the literature. Therefore, in the consequent, qualitative phase, the researchers conducted semi-structured interviews among nine, purposefully selected respondents and focused on the factors explaining the dissimilar influence of anxiety on L2 speaking and writing. Results exposed the double-edged nature of anxiety within the study’s context. On one hand, social comparison-instigated anxiety debilitated speaking task performance. On the other, grade anxiety facilitated constant correction, which aided the engineering students in writing task performance. Besides implication for research, the pedagogical implications of the results in relation to teaching engineering students as learners of English are provided.